Sistem Informasi Persediaan Barang Berbasis Web (Studi Kasus PT.Metro Akses Pratama) - Lutfi Bimantoro; Ina Sholihah Widiati; Febrianta Surya Nugraha (Yayasan Literasi Sains Indonesia, 2022)
The use of computers in information technology has become a necessity in various business fields. The ability of computers in processing reports and storing data makes many companies use them for data processing purposes. The role of computers is needed in various fields, both institutions and companies. PT. METRO AKSES PRATAMA which was established in 2011 is engaged in ISP, to serve home and corporate customers throughout Indonesia. Currently the system that is running still has many shortcomings, namely recording goods and compiling reports of incoming and outgoing goods that are still manually using paper or books causing the company's performance to be hampered, frequent data loss and data damage and not being able to support all the needs the company wants. This web-based inventory system is used to produce the system needed by PT. METRO AKSES PRATAMA in processing the inventory process and simplifying the data processing. By using this application the Manager can find out the data of goods, data of incoming goods, data of goods out of it and can directly print all related reports per period (1 month).